Global NAVIGATION Satellite System Contribution for Observing the Tectonic Plate Movements: Status and Perspectives (Journal of Engineering, 2014)
The long-term monitoring of land movements represents the most successful application of the Global Navigation Satellite System (GNSS), particularly the Global Positioning System. However, the application of long term monitoring of land movements depends on the availability of homogenous and consistent daily position time series of stations over a period of time. Such time series can be produced very efficiently by using Precise Point Positioning and Double Difference techniques based on particular sophisticated GNSS processing softwares. Nonetheless, these rely on the availability of GNSS products which are precise satellite orbit and clock, and Earth orientation parameters. Unfortunately, several changes and modifications have been made periodically on the policy of producing these products which led to degradation in the consistency of these products over time. For the long term monitoring of land movements, it is essential that any such developments and changes can also be used to produce improved products that go back in time, to enable the homogeneous reprocessing of archived observation data. This paper deals with two main themes. Firstly, it demonstrates the significant and imperative role of the GNSS in geological applications by addressing major global and regional studies of the Earth’s deformation which represent one of the main and essential applications in satellite geodesy. The role of the continues GPS measurements in this application is highlighted and discussed for modeling global and regional plate motions and modeling Glacial Isostatic Adjustment. Secondly, this paper locates the most important obstacles which stand behind the inability to use the GNSS in applications of long-term monitoring of land movements.